2012
DOI: 10.1080/17461391.2012.691117
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the ACE, PPARGC1A and PPARA genes in Lithuanian football players

Abstract: The aim of this study was to determine the impact of ACE (I/D), PPARGC1A (G/A) and PPARA (G/C) polymorphisms on footballers performance among 199 Lithuanian professional footballers and 167 sedentary, healthy men (controls). Genotyping was performed using polymerase chain reaction and restriction fragment length polymorphism methods on DNA from leucocytes. Results revealed that the angiotensin-1-coverting enzyme gene (ACE) genotype distribution was significantly different between total football players group (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 28 publications
6
48
1
1
Order By: Relevance
“…Our results (II = 17%; ID = 50%; e DD = 33%) are in agreement with previous studies (Gineviciene et al 2012;Juffer et al 2009) which found that the ACE-I/D genotype distribution of soccer players was similar to that of the general population, but they do not confirm the results by Massidda et al (2012), who reported that the frequency of the DD genotype was predominant in both athletes and controls.…”
Section: [Digite Texto]supporting
confidence: 66%
See 1 more Smart Citation
“…Our results (II = 17%; ID = 50%; e DD = 33%) are in agreement with previous studies (Gineviciene et al 2012;Juffer et al 2009) which found that the ACE-I/D genotype distribution of soccer players was similar to that of the general population, but they do not confirm the results by Massidda et al (2012), who reported that the frequency of the DD genotype was predominant in both athletes and controls.…”
Section: [Digite Texto]supporting
confidence: 66%
“…Soccer is classified as an intermittent and highly intense activity (Coelho et al 2011) and therefore performance of soccer players is directly influenced by the power, speed and strength capacities of the players. Ahmetov et al (2008) suggested that there might be a natural selection for high performance sports, according to the predominance of aerobic or anaerobic capacities (power, speed, strength, endurance), while in soccer all these capacities combined may be responsible for the natural selection (Gineviciene et al 2012;Juffer et al 2009;Eynon et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows that participants in most of the studies were Euro-Slavic with three (Australia, Japan and Korea) contributing to geographical heterogeneity [30, 32, 38]. Subgroups by sport type and race comprised of power [26, 27, 29, 34, 35], endurance [25-27, 30, 31, 33-36, 38] and mixed [27, 28, 32, 34, 37], Caucasian [25-30, 33-37] and Asian [31, 32, 38], respectively. Median and range CB score of 7.0 (5-9) indicates that methodological quality of the component studies was high.…”
Section: Resultsmentioning
confidence: 99%
“…Polymorphisms in α-actinin-3 (ACTN3) and angiotensin I converting enzyme (ACE) genes are associated with power and endurance abilities, respectively [3,4]. A premature stop codon SNP (p.Arg577Ter, rs1815739) in ACTN3 leads to a lower level of α-actinin-3.…”
Section: Introductionmentioning
confidence: 99%